A Heuristic Science-Based Naturalism as a Partner for Theological Reflections on the Natural World - D'Ambrosio, Paolo (Zygon, 2015)
After a few general observations on scientific activity, the author briefly comments on different versions of naturalism. Subsequently, he suggests that the birth of evolutionary biology and its successive developments may show how the natural world comes to be differently conceived as scientific advancements are accomplished. Then the main thesis is outlined by introducing the principles of a heuristic science-based naturalism not conclusively defining the real and the knowable. From the epistemological perspective, heuristic naturalism is meant to be framed in critical realism, whereas from the ontological standpoint it may be framed in emergent monism, given that the latter can also underpin recent trends in investigation addressing human specificity. Finally, attention is turned to some implications of heuristically guided scientific activity with regard to the issues of divine action and of imago Dei.